Environmental perception studies: a phenomenological approach - Zanini, Alanza Mara (2021)
The current outlook of the environmental crisis highlights the importance to the exercise of each subject's own understanding, that stems from the individual interpretation of the space surrounding us reflected by theirs historical-cultural context. Thus, studies of environmental perception stand out as an important strategy to know the relationship between human beings and nature, in order to provide a reflective study of the issues environmental. The phenomenological perspective is related to environmental perception studies, as it considers the individual ways of feeling and perceiving the lived space. In this sense, this study attempts to reflect about the importance of environmental perception studies and their dialectical, axiological and phenomenological aspects, with regard to formal and non-formal education. We believe that it is possible, with the contributions of environmental perception to the formal and non-formal education, to reinvent a social order that is more just, democratic and environmentally safe.